The Correlation and Regression Analysis of Physicochemical Parameters of River Water for the Evaluation of Percentage Contribution to Electrical Conductivity - Arun Kumar Shrestha; Nabin Basnet (Journal of Chemistry)
Ten different water samples were collected from Ratuwa River and its tributaries. The laboratory test was carried out by standard procedures (APHA methods), and the measured values were compared with the Nepal standard recommended by Nepal Drinking Water Quality Standards (NDWQS). Statistical analysis also had been used to calculate the correlation coefficients and to plot the regression equations of various parameters with electrical conductivity. The aim of the study was to identify the parameters that affect the electrical conductivity and evaluate the percentage contribution of these parameters. The correlation matrix shows that color, total dissolved solids (TDS), chloride (Cl), fluoride (F), total phosphorus (TP), total alkalinity (TA), calcium (Ca), magnesium (Mg), sodium (Na), and dissolved oxygen (DO) have a significant effect on the electrical conductivity (EC). Among these parameters, TDS has the highest contribution (39.65%) followed by total alkalinity (23.5%), total hardness (19.9%), chlorine (6.5%), and calcium (5.5%) ions, respectively. However, color, TP, fluoride, and DO have almost 1.45% contribution to the electrical conductivity.